Implementation Knowledge Management in X Division Case Study : PT. Bank XYZ - Wiguna, Prayuda; Hidajat Tjakraatmadja, Jann (The Indonesian Journal of Business Administration, 2016)
Abstract - IT Division at PT. Bank XYZ is one of the companyâ€™s backbones and its performance will affect the achievement of PT. Bank XYZ. PT. Bank XYZ relies heavily on technology in running business. Knowledge management can improve a company's competitive advantages. Combination between IT and Knowledge Management will be a good combination to increase the competitive advantages for PT. Bank XYZ. This study aims to improve the achievement of X Division by implementing Knowledge Management in order to anticipate losing knowledge in X Division, decreasing dependencies on key persons, increasing externalization knowledge in X Division, optimize Knowledge Management Documentation and Knowledge Management system. Exploration of business issues that occur in X Division seen by four components of Knowledge Management named people, process, technology and governance. By using SWOT analysis and Fishbone methodology this research found a strategy that can be implemented in X Division. The strategy is to apply the Knowledge Management by following five steps include KM determining objectives, 9 answering questions, defining KM strategy, obtaining management and implementation plan. This implementation is expected to enhance the achievement of X Division and has positive affect to the performance of PT. Bank XYZ.Â Key words: Competitive Advantages, Knowledge Management, Achievement, Improvement, Implementation of Knowledge Management